Facts about Fiber - Jennifer Hillan; R. Elaine Turner (EDIS)
FCS-8793, a 2-page illustrated fact sheet by Jennifer Hillan and R. Elaine Turner, provides nutritional information about fiber. Published by the UF Department of Family Youth and Community Sciences, April 2006.